PERANCANGAN SISTEM INFORMASI SEKOLAH MENENGAH ATAS KRISTEN KASIH KEMULIAAN BERBASIS WEB - Daniel Hadiyanto; Desi Arisandi; Wasino Wasino (Jurnal Ilmu Komputer dan Sistem Informasi, 2022)
The world has entered the era of digitalization where information technology is growing very rapidly, especially technology related to the internet. Almost every aspect of life uses the internet as a practical and worldwide information medium. With the development of information technology, many things can be produced in certain fields including education; such as creating a website to advertise schools and/or campuses so that more people are known to be interested in registering their children so they can continue their education, creating a database containing a list of school/academic grades to monitor the progress of students who determine their graduation correctly. and accurate, or save teaching materials online so that they are easy to learn when learning must be online, etc. In this case, SMAK Kasih Kemuliaan utilizes the internet network to introduce information about the school as completely and interestingly as possible. Thus the school can be known by the wider community and even abroad. The information technology used by SMAK Kasih Kemuliaan is the school's web profile as complete as possible, besides that the public is expected to be able to access school information easily and efficiently. By using the school's web profile, it is hoped that prospective high school students will get the school they expect. Thus, SMAK Kasih Kemuliaan can be their main goal. With the increasing number of new students at SMAK Kasih Kemuliaan, the school will progress and develop, not closing the hope of becoming one of the leading schools.